1994
DOI: 10.1002/ijc.2910580411
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine nucleotide metabolism in human colon carcinomas: Comparison of normal tissues, primary tumors and xenografts

Abstract: The activities of 5 enzymes involved in the pyrimidine metabolism were measured in xenografts of 8 human colon adenocarcinomas and in the corresponding primary tumors and normal tissues. The enzymes studied were thymidine kinase, thymidine phosphorylase, uridine kinase, uridine phosphorylase and thymidylate synthase. With the exception of the phosphorylases in one tumor, all enzyme activities were higher in primary tumors than in the corresponding normal tissues. The average activities of thymidine kinase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
2
19
1
Order By: Relevance
“…When the human colon cancer cell line, WiDr, was incubated with paclitaxel, docetaxel, or mitomycin C, or tumor necrosis factor-related apoptosis-inducing ligand, each agent greatly induced TP (27). However, a decrease in TP activity in xenografts compared with primary tumors means that care is needed when extrapolating findings to the clinical setting (28).…”
Section: Discussionmentioning
confidence: 99%
“…When the human colon cancer cell line, WiDr, was incubated with paclitaxel, docetaxel, or mitomycin C, or tumor necrosis factor-related apoptosis-inducing ligand, each agent greatly induced TP (27). However, a decrease in TP activity in xenografts compared with primary tumors means that care is needed when extrapolating findings to the clinical setting (28).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly less is known about the corresponding actions of TP, despite evidence that it is overexpressed in a large percentage and wide range of human solid tumors (22)(23)(24)(25)(26). Recent studies suggest that there are similarities in the transcriptional regulation of TP and VEGF, and there is a tendency for VEGF and TP to be co-expressed in some human cancers (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…TP is chemotactic for endothelial cells and has angiogenic activity in several in vivo assays, although it did not directly stimulate endothelial cell proliferation (16 -20). Studies have established a role for TP in experimental and clinical tumor angiogenesis, including transfection studies in which the TP gene increased the vascularization and growth of tumors growing in nude mice (20,21), and immunohistochemical studies of primary human solid tumors, in which TP was often found to be elevated in the tumors when compared with the corresponding nonneoplastic regions of the same organs (22)(23)(24)(25)(26). The mechanism by which TP mediates angiogenesis is unknown; we have used endothelial cell migration as an in vitro model to address this question.…”
mentioning
confidence: 99%
“…It is not clear whether this is due to its release from the tumour itself or production and release by host cells and tissues in response to tumour growth/proliferation. Activity of another pyrimidine phosphorylase, UrdPase, has also been reported to be elevated in primary human tumours, including colon (Luccioni et al, 1994) and melanoma (Leyva et al, 1983). One study in human colon carcinoma has suggested PNP activity is also enhanced and suggests a positive relationship with enzyme activity and tumour invasiveness (Sanflippo et al, 1994).…”
Section: In Vivo Localization Of Pd-ecgf/dthdpasementioning
confidence: 99%